Equilibrium inter-mineral titanium isotope fractionation: Implication for high-temperature titanium isotope geochemistry. (15th January 2020) - Wang, Wenzhong; Huang, Shichun; Huang, Fang; Zhao, Xinmiao; Wu, Zhongqing
Abstract: Equilibrium Ti isotope fractionation factors among major Ti-bearing minerals are critical for understanding Ti isotope fractionation during magmatic processes. We use the first-principles calculations based on the density functional theory (DFT) to obtain Ti isotope reduced partition function ratios (10 3 lnβ of 49 Ti/ 47 Ti) in a series of important Ti-bearing minerals, including Ti-doped clinopyroxene, orthopyroxene, olivine, and pyrope, geikielite-ilmenite solid solutions, and rutile. There is a large variation in our calculated 10 3 lnβ, which are linearly correlated to their Ti force constants, a parameter related to the average TiO bond length and the Ti valence state. Among all studied minerals, silicates with Ti 4+ occupying the tetrahedral Si site have the highest 10 3 lnβ, and rutile has the lowest 10 3 lnβ. The valence state also significantly controls the 10 3 lnβ. Typically, Ti 3+ -doped silicates have lower 10 3 lnβ than those of Ti 4+ -doped silicates. At the natural abundance levels, the 10 3 lnβ of Ti 4+ Si -doped and Ti 3+ Mg -doped (Ti 3+ occupying the Mg site) silicate minerals show no concentration effect. That is, their 10 3 lnβ do not vary with their Ti 4+ and Ti 3+ contents, respectively. In contrast, the 10 3 lnβ of geikielite-ilmenite solutions significantly decrease with increasing Fe/(Fe + Mg) ratio. Our calculations predict no significant Ti isotope fractionation among Ti 4+ Si -doped clinopyroxene, orthopyroxene, olivine, and pyrope (<0.08 % at 1200 K), whereas the 10 3 lnα between geikielite-ilmenite solutions and Ti 4+ Si -doped clinopyroxene ranges from ∼−0.67‰ to −0.49‰ at 1200 K, supporting the hypothesis that FeTi oxides are important fractionating Ti isotopes during magma differentiation. Finally, the large equilibrium Ti isotope fractionation between geikielite-ilmenite solutions and clinopyroxene suggests that Ti isotopes can be used as a thermometer with precision comparable to that of elemental geothermometer.